Penguatan Peran Pemerintah Desa Cileles dalam Membangun Usaha Mikro Kecil (UMK) - Mulyana Mulyana; Agung Nurrahman; Abdurohim Abdurohim (Civitas Consecratio: Journal of Community Service and Empowerment, 2021)
The low role of the Cileles Village Government in assisting UMK actors in running their business is the focus of the problems raised in community service activities. The purpose of community service activities is to strengthen the role of the Village Government in Cileles Village in building MSEs in Cileles Village. The methods in community service activities (PKM) include the use of socialization methods, delivery of materials and open dialogue with the Cileles Village Government, members of the Village Consultative Body (BPD), RT/RW leaders, and the UMK community actors in Cileles Village. The results of the service activities are:1) there are outputs in the form of strengthening the role of the Cileles Village Government as a regulator and issuing a draft of the Cileles Village Regulation on the “Cileles Sejahtera” Village UMK Management Clinic; 2) as a dynamist, there is an open dialogue between IPDN academics and the community regardingMSE issues; 3) as a facilitator, the output is the compilation of an inventory of the types of training and their benefits that can be carried out by the Cileles Village Government in collaboration with academics and business people; 4) as a catalyst in building UMK in Cileles Village is the delivery of business informationby IPDN academics to UMK actors in delivering the material that has been done. The conclusion of the PKM activity is that the Cileles Village Government and the community of UMK actors welcome and provide a positive response regarding the establishment of a UMK management clinic in Cileles Village, as a forum for UMK actors to consult and innovate, as well as a forum for the Village Government to strengthen its role in assisting business implementation. UMK actors in Cileles Village in the long term.